At Ta'bir Asy Syafahi wa Manzilatuhu baina Furu'il Lughah - Syarifah Rizcy; Saproni M Samin; Rojja Pebrian ((الطموحات ) EL-THUMUHAT, 2019)
The importance of expression in the teaching of Arabic is the goal of studying all branches of the language. The importance of expression as a means of communication with others is one aspect of the process of understanding. Expression is not just a set of language skills that any student must master so that he can express what he wants but to express a dimension other than this linguistic dimension, the cognitive dimension. Speech is the second skill of language skills after listening and not every voice speech because speech must be available two words and a benefit, and the voice is composed of some letters, and benefit is what the meaning of meanings in the minds of speakers as expressed by Arab linguists. One of the most important teaching of any language is to speak or express thoughts, feelings and attitudes in the mind, and to confront everyday communication situations. However, the oral expression in the process of teaching the language levels.